From a strategy of charm to civil power: soft power in China and the European Union - Tzili Apango, Eduardo (Estudios Internacionales, 2011)
Given the erosion of the American hard power at the beginning of the 21st century, it emerges two actors which trough its soft power became necessary reference to both developing and developed countries. I am referring to the European Union and China. However, will both European and Chinese soft power be the same? Which soft power is becoming stronger in the global arena? And more emphatically: will soft power be the only effective means to acquire the status pursued by China as well as by the European Union? This paper will attempt to provide an answer in the face of these uncertainties.